Determinants of commercial banks interest rate spreads in the multiple currency environment in Zimbabwe - Makotore, Prosper (Midlands State University, 2015)
The study focused on the determinants of bank spreads in Zimbabwe’s commercial banking sector in the multiple currency period (2009 to 2012). The study employed panel data techniques to analyze the impact of bank specific, industry specific and macroeconomic factors on bank spreads. Other objectives of the study involved the study of the contribution of foreign and local banks to widening bank spreads and to establish the relationship between the spread and its components the deposit rate and the lending rate. The main literature of the study comprised of theoretical and empirical literature from related studies that were done in developing nations. A quantitative technique was adopted in carrying out this research where statistical secondary data was collected from financial statements, Reserve Bank of Zimbabwe and Zimstats. Pooled ordinary least squares was used to estimate the model using the econometric package e-views 5.1. The variables used to estimate the model were chosen from literature and they are overhead costs, non-interest income, non-performing loans, market share of deposits, capital adequacy and inflation. Results obtained indicated that bank spreads are high in Zimbabwe and they are mostly driven by overhead costs, non-performing loans, and market share of deposits, capital adequacy, bank size, and inflation. There was no evidence to support the impact of non-interest income on bank spreads. Foreign banks charged lower spreads than local banks in the same period. Lending rates were highly volatile as compared to deposit rates. The study recommends policies to increase competition, operational efficiency, strengthening local banks, and adopting partial dollarization. Further studies were recommended in the areas of the impact of the monetary policy in explaining bank spreads